Is the acquired hypothyroidism a risk factor for developing psychiatric disorders? - Osnaya-Brizuela, Norma; Valenzuela-Peraza, Armando; Santamaría-del Ángel, Daniel; García-Martínez, Yuliana; Pacheco-Rosado, Jorge; Pérez-Sánchez, Gilberto; Sánchez-Huerta, Karla (Frontiers in Psychiatry, 2024)
Hypothyroidism is a prevalent thyroid condition in which the thyroid gland fails to secrete an adequate amount of thyroid hormone into the bloodstream. This condition may develop due to genetic or acquired factors. The most frequent cause of acquired hypothyroidism is chronic autoimmune thyroiditis, also known as Hashimoto's disease. Acquired hypothyroidism is diagnosed when patients present with overt hypothyroidism (also known as clinical hypothyroidism), as they exhibit increased TSH and decreased T3 and T4 serum levels. This article examines the prevalence of psychiatric disorders among patients diagnosed with acquired hypothyroidism with or without Levothyroxine treatment. We discuss the available evidence indicating that acquired hypothyroidism may be a risk factor for psychiatric disorders, and the effectiveness of thyroid treatment in relieving psychiatric symptoms. Additionally, we provide critical details on thyroid hormone cutoff values reported in the literature, their potential clinical importance, and their correlation with psychiatric symptoms.Finally, we examined the various mechanisms by which acquired hypothyroidism can lead to depression. The high rate of comorbidity between hypothyroidism and psychiatric disorders deserves special attention, indicating the importance of consistent monitoring and timely identification of psychiatric symptoms to prevent disease exacerbation and facilitate therapeutic management. On the other hand, several mechanisms underlie the strong association between depression and acquired hypothyroidism. Deeper research into these mechanisms will allow knowledge of the pathophysiology of depression in patients with acquired hypothyroidism and will provide clues to design more precise therapeutic strategies for these patients.